plzz answer it quickly anyone
Attachments:
![](https://hi-static.z-dn.net/files/d3e/bce3b25ca8257e3e748b75c58bc60df4.jpg)
Answers
Answered by
0
hey mate and here is ur answer
![\frac{2 {}^{m - n} }{2 {}^{n - m} } \frac{2 {}^{m - n} }{2 {}^{n - m} }](https://tex.z-dn.net/?f=+%5Cfrac%7B2+%7B%7D%5E%7Bm+-+n%7D+%7D%7B2+%7B%7D%5E%7Bn+-+m%7D+%7D+)
=
![2 {}^{m + n - n + m} 2 {}^{m + n - n + m}](https://tex.z-dn.net/?f=2+%7B%7D%5E%7Bm+%2B+n+-+n+%2B+m%7D+)
=
![2 {}^{2m} 2 {}^{2m}](https://tex.z-dn.net/?f=2+%7B%7D%5E%7B2m%7D+)
=16
m=2
n=0
=
=
=16
m=2
n=0
Attachments:
![](https://hi-static.z-dn.net/files/da9/b0baf7e2829259c76f1ac83e45b168e9.jpg)
braniaco:
plz see the full question
Similar questions
Hindi,
7 months ago
Hindi,
7 months ago
English,
7 months ago
Political Science,
1 year ago
Math,
1 year ago
Social Sciences,
1 year ago
Social Sciences,
1 year ago